2010
DOI: 10.1016/j.jtcvs.2010.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outcome after surgical treatment of pulmonary atresia with ventricular septal defect and major aortopulmonary collateral arteries

Abstract: Objectives: Identification of variables influencing surgical outcome in patients treated for pulmonary atresia with ventricular septal defect and major aortopulmonary collateral arteries. Methods: A total of 90 consecutive patients (median age, 12 months; range, 20 days to 35 years), who had primarily undergone either 1-stage unifocalization (n ¼ 69) or palliation to promote native pulmonary arterial development (n ¼ 21), were studied. Chromosome 22q11 deletion had occurred in 37% of the cases. Ventricular sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 26 publications
5
103
1
Order By: Relevance
“…One aspect of this diversity is the variable anatomy of the central branch pulmonary arteries [2][3][4][5]. Approximately 80% of patients with PA/VSD/MAPCAs have central branch pulmonary arteries, whereas 20% of patients have a complete absence of intrapericardial pulmonary arteries [6][7][8][9][10][11]. The developmental factors resulting in the presence or absence of central pulmonary arteries in PA/VSD/MAPCAs are currently not well defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect of this diversity is the variable anatomy of the central branch pulmonary arteries [2][3][4][5]. Approximately 80% of patients with PA/VSD/MAPCAs have central branch pulmonary arteries, whereas 20% of patients have a complete absence of intrapericardial pulmonary arteries [6][7][8][9][10][11]. The developmental factors resulting in the presence or absence of central pulmonary arteries in PA/VSD/MAPCAs are currently not well defined.…”
mentioning
confidence: 99%
“…Several groups continue to advocate the use of either a central shunt or right ventricle to pulmonary artery conduit as the principal method to achieve "pulmonary artery rehabilitation" [12][13][14][15][16]. The central pulmonary arteries can also be utilized in conjunction with unifocalization of MAPCAs for repair of PA/VSD/MAPCAs [6][7][8][9][10][11][17][18][19]. This strategy provides a versatile approach to the management of PA/VSD/MAPCAs and has yielded excellent hemodynamic results [20].…”
mentioning
confidence: 99%
“…The major reasons for the excellent detection of pulmonary arterial morphology with CT in this study might be (1) sufficient distribution of contrast medium in the patent part of pulmonary arteries distal to the atretic segment from several cardiac cycles in CT, (2) volumetric data acquisition in CT that prevent an overlapping shadow in projection [20,24,26], and (3) atretic stump of the pulmonary trunk is sometimes enhanced only by retrograde flow or inadequately filled in ductal angiography or descending aortogram, which has only a limited contrast medium-enhanced vascular shadow [7,27]. The adequate demonstration of pulmonary arterial aborization should be beneficial to repair TOF-PA [3,17,28,29]. For example, Carotti et al [3] demonstrated that the absence of confluent intrapericardial pulmonary arteries affected the postoperative right/left ventricular pressure ratio after ventricular septal defect closure, and the right/ left ventricular pressure ratio has been shown the most powerful factor related to survival in patients with TOF-PA [19].…”
Section: Discussionmentioning
confidence: 99%
“…The adequate demonstration of pulmonary arterial aborization should be beneficial to repair TOF-PA [3,17,28,29]. For example, Carotti et al [3] demonstrated that the absence of confluent intrapericardial pulmonary arteries affected the postoperative right/left ventricular pressure ratio after ventricular septal defect closure, and the right/ left ventricular pressure ratio has been shown the most powerful factor related to survival in patients with TOF-PA [19]. Selective angiograms with the injection of contrast medium in the ductus arteriosus are usually suggested to identify the confluence of pulmonary arteries [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation